Using Conversation Analysis to explore assessments of decision‐making capacity in a hospital setting - Foulkes, Jessica; Volkmer, Anna; Beeke, Suzanne (International journal of language & communication disorders, 2024)
Background Healthcare professionals (HCPs) have a responsibility to conduct assessments of decision‐making capacity that comply with the Mental Capacity Act 2005 (MCA). Current best‐practice guidance, such as the Mental Capacity Code of Practice and National Institute for Health and Care Excellence decision‐making and mental capacity guidance, does not stipulate how to accomplish this in practice, for example, what questions should be asked, how options and information should be provided. In addition, HCPs struggle to assess the capacity of individuals with communication difficulties. Aims This study was a service evaluation that aimed to objectively analyse, using Conversation Analysis (CA), how real‐life capacity assessments were conducted in a hospital setting with patients with acquired brain injury (ABI)‐related communication difficulties. A second aim was to establish the feasibility of using CA to advance knowledge of the conduct of capacity assessment. Methods & Procedures Four naturally occurring capacity assessments were video‐recorded. Recordings involved speech and language therapists, occupational therapists, neuropsychologists and patients with communication difficulties as a result of ABI. The methods and findings of CA were used to investigate the interactional behaviours of HCPs and patients during assessments of decision‐making capacity. The analysis was informed by our knowledge of the MCA best practice guidance. Outcomes & Results An overall structure of capacity assessment that enacted some of the best‐practice MCA guidance was identified in one recording, consisting of six phases: (i) opening, (ii) preparation, (iii) option‐listing, (iv) test, (v) decision, and (vi) close. The preparation phase consisted of two sub‐components: information gathering and information giving. Variation from this structure was observed across the dataset, notably in the way in which options were (or were not) presented. Conclusions & Implications CA is a feasible empirical method for exploring the structure and conduct of capacity assessments. CA identifies and provides ways of describing interactional behaviours that align with and diverge from best‐practice MCA guidance. Future CA studies including a wider range of health and social care professionals and patients have the potential to inform evidence based training for HCPs who conduct assessments of decision‐making capacity. WHAT THIS PAPER ADDS What is already known on this subject The Mental Capacity Act (MCA) is poorly implemented in practice. Healthcare professionals (HCPs) find it challenging to assess the decision‐making capacity of individuals with communication difficulties, and people with communication difficulties are often excluded from or insufficiently supported during capacity assessment. Research is limited to self‐report methods. Observational studies of capacity assessment are required. What this study adds This is the first study to use Conversation Analysis (CA) to explore how capacity assessments are conducted in a hospital setting by HCPs with people with communication difficulties as a result of acquired brain injury. One video‐recorded capacity assessment was structured in six phases that aligned with best practice MCA guidance. However, other capacity assessments deviated from this structure. One phase, option listing, varied in practice and options were not always presented. What are the clinical implications of this work? CA revealed interactional behaviours that align with and diverge from best‐practice MCA guidance. Future CA studies are warranted to inform training for health and social care professionals who conduct capacity assessments.